المخارج الشرعية في المصرفية الإسلامية : دراسة تقويمية - أحمد، شبيرأحمد بن مولوي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Islamic banking has found in the Shari'ah Makharij (Exit Options) solutions to the obstacles it is facing. However, these solutions are weighed down with lots of criticisms since they are considered as “prohibited hiyal (subterfuge)” which leads to many gray area as far as the shariah Makharij is concerned. This study “Shari'ah Makharij (Devices) in Islamic Banking – An Evaluative Study” was conducted with the aims to understand reality of these Sharia devices and of their application in Islamic Banking. This study explained the meaning of Shari'ah Makharij (Devices) according to the classical views and the contemporary Sharia scholars. This study illustrated application of these Shari'ah Makharij (Devices) in banking services and finances by Al Rajhi Bank in Malaysia and evaluated their implementation and provisions and alternative solutions according to the Shari'a. The researcher in this study followed inductive, narrative, analytical and critical approaches. The research concluded that Shari'ah Makharij (Devices) are “use of legitimate hidden method to avoid sins and hardships without resulting in change of the Sharia rules or contradicting with the objective/intention of the legislator”. It was found that they are type of Hiyal (subterfuges) in in their general meanings but are different in various essential aspects from the subterfuges in. The study also found that the Shari'a devices started at the time of the prophet and developed at the era of compilation (Tadween) and Mujtahid scholars and thereafter independent books were written in this regards and the Islamic Banks relied on these Shari'ah devices. Shari'ah Makharij (Devices) and these devices have various types due to different considerations. Scholars have agreed on legitimacy provided they are regulated by Sharia principles standards, but disagreed on widening application of the Shari'ah devices. On the practical side of the research, it concluded that Sharia contracts relied upon in Al Rajhi Bank Malaysia, breach existing conventional banking transactions. There involve, particularly, Qard (loan), Wakala (agency) and Commodity Murabaha (Tawarruq), Murabaha to orderer, Al Kafala (guarantee), Sarf (currency exchange), Ijarah (lease) and wages against work, etc. The study found that most consumer based finance facilities such as personal financing, property financing and commercial financing are based on commodity Murabaha (Tawarruq), and that the investment accounts are based on reverse Tawarruq. All these are not free of Sharia issues and since auto finance is based on Murabaha to orderer has found to be compatible with sharia compliance. It was also found that most Shari'ah devices adopted in retail and commercial banking services are free from Shari'ah related issues, and are fully Sharia compliant.